Ethical Considerations When Counseling Patients About Stem Cell Tourism. Issue 1 (February 2015) - Tsou, Amy
Abstract : ABSTRACT: Worldwide, many clinics market stem-cell based interventions often touted as effective for many diseases including spinal cord injury, multiple sclerosis (MS), and other neurodegenerative diseases. These clinics and their expensive, unproven treatments continue to fuel the practice of stem cell tourism. Given concerns about patient exploitation and safety, how should the physician engage a patient who wants to pursue such treatments? This article presents the case of a patient with neuromyelitis optica interested in pursuing expensive stem cell injections abroad. This article describes stem cell tourism along with some of the ethical issues physicians should consider, while also providing practical resources that physicians may employ to educate and engage patients in making an informed decision.